Literature Review : Building Trust Sharing Accommodation - Renoati, Anindhita Dipa; Septiari, Elisabet Dita (International Journal of Business, Law, and Education, 2025)
Trust is an important element in the success of accommodation sharing platforms like Airbnb. This study aims to identify and analyze factors that can affect the formation of user trust in the platform. The approach used in this study is a literature review, by collecting and analyzing various relevant studies from Scopus indexed journals in the period of 2019 – 2024. The results of the study show that trust is formed through three main phases, namely before, during, and after the stay. Information transparency, social reviews, and security assurance are important factors in the early phases, while direct interaction with hosts and local experiences reinforce trust during a stay. The bilateral review system and the platform's response to user complaints are key in maintaining user loyalty after a stay. However, the study was limited to Europe and North America so it did not fully reflect Asian cultures that were more group-oriented. Future research is suggested to expand geographical coverage, utilize innovative technology, and examine longitudinal changes in beliefs. The findings of this study provide guidance for platforms to improve user trust and business sustainability.